Emphasizing the Role of Neurosurgery Within Global Health and National Health Systems: A Call to Action - Lartigue, Jean Wilguens; Dada, Olaoluwa Ezekiel; Haq, Makinah; Rapaport, Sarah; Sebopelo, Lorraine Arabang; Ooi, Setthasorn Zhi Yang; Senyuy, Wah Praise; Sarpong, Kwadwo; Vital, Anchelo; Khan, Tariq; Karekezi, Claire; Park, Kee B. (Frontiers in Surgery, 2021)
Background: Worldwide, neurological disorders are the leading cause of disability-adjusted life years lost and the second leading cause of death. Despite global health capacity-building efforts, each year, 22.6 million individuals worldwide require neurosurgeon's care due to diseases such as traumatic brain injury and hydrocephalus, and 13.8 million of these individuals require surgery. It is clear that neurosurgical care is indispensable in both national and international public health discussions. This study highlights the role neurosurgeons can play in supporting the global health agenda, national surgical plans, and health strengthening systems (HSS) interventions. Methods: Guided by a literature review, the authors discuss key topics such as the global burden of neurosurgical diseases, the current state of neurosurgical care around the world and the inherent benefits of strong neurosurgical capability for health systems. Results: Neurosurgical diseases make up an important part of the global burden of diseases. Many neurosurgeons possess the sustained passion, resilience, and leadership needed to advocate for improved neurosurgical care worldwide. Neurosurgical care has been linked to 14 of the 17 Sustainable Development Goals (SDGs), thus highlighting the tremendous impact neurosurgeons can have upon HSS initiatives. Conclusion: We recommend policymakers and global health actors to: (i) increase the involvement of neurosurgeons within the global health dialogue; (ii) involve neurosurgeons in the national surgical system strengthening process; (iii) integrate neurosurgical care within the global surgery movement; and (iv) promote the training and education of neurosurgeons, especially those residing in Low-and middle-income countries, in the field of global public health.